1999
DOI: 10.1161/01.atv.19.3.734
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Interleukin 12 in the Development of Atherosclerosis in ApoE-Deficient Mice

Abstract: Abstract-The cytokine profile of atherosclerotic aortas from apoE-deficient mice was assessed by reverse transcriptasepolymerase chain reaction. The results clearly showed that the expression of mRNA for IL-12p40 was evident in aortas from 3-month-old apoE-deficient mice. The mRNA for IL-10 was detected in aorta from these mice at the age of 6 months, indicating that expression of IL-12 is earlier than that of IL-10 in these animals. Concurrent with IL-12p40, the mRNA for the T-cell cytokine IFN-␥, but not IL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
183
1
10

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 282 publications
(201 citation statements)
references
References 57 publications
7
183
1
10
Order By: Relevance
“…In contrast, Th2 cells, which antagonize Th1 function (7), may serve to impede the development of atherosclerotic lesions. Consistent with this notion, IL-12, a potent Th1 inducer, has been shown to promote atherogenesis (45,48). In contrast, IL-10, a potent Th2 cytokine, has been shown to antagonize atherogenesis (46)(47)(48)(49).…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…In contrast, Th2 cells, which antagonize Th1 function (7), may serve to impede the development of atherosclerotic lesions. Consistent with this notion, IL-12, a potent Th1 inducer, has been shown to promote atherogenesis (45,48). In contrast, IL-10, a potent Th2 cytokine, has been shown to antagonize atherogenesis (46)(47)(48)(49).…”
Section: Discussionmentioning
confidence: 87%
“…The development of murine models has provided an opportunity to evaluate the potential role of these immune cells in disease pathogenesis (12). Recent studies in mice have demonstrated that macrophages and two T cell activators, CD40 and IL-12, effectively promote atherogenesis (13,21,45); and that IL-10, a known T cell antagonist, appears to moderate atherogenesis (46)(47)(48)(49). Moreover, IFN-γ, a potent proinflammatory T cell effector, has also been shown to promote atherogenesis (2,5,22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, adaptive responses to OxLDL have been shown to increase during disease progression, but their exact role in atherogenesis is uncertain (18,19). Notably, in cholesterol-fed apoE -/-mice, advanced stages of atherosclerosis are associated with increased accumulation of OxLDL (20), and in this setting there is an immune deviation of OxLDL-specific Th1 responses toward Th2 (21,22). The Th2 cytokine IL-4 has been reported to have either pro-or anti-atherogenic effects (23)(24)(25), whereas IL-10 secretion by T cells decreases atherogenesis (26,27).…”
Section: Introductionmentioning
confidence: 99%
“…En outre, la quantité d'interleukine (IL)-18, un inducteur de la production d'IFN-γ présent dans les plaques carotides humaines, est positivement corrélée à l'instabilité clinique (présence d'accident vasculaire céré-bral) et anatomique (présence d'ulcération) de la lésion [10]. L'injection à des souris apoE -/-d'IL-18 ou d'IL-12, une autre cytokine pro-inflammatoire néces-saire à l'induction de la production d'IFN-γ, augmente significativement la taille des plaques, qui deviennent alors très riches en cellules inflammatoires et présen-tent un phénotype instable [9,11]. D'autres voies inflammatoires, comme celle impliquant l'interaction entre le récepteur CD40 et son ligand, sont également importantes pour la progression et l'instabilité des plaques [12].…”
Section: Réponse Inflammatoire Et Remodelage Matricielunclassified